A social realist ontology for developing Afrocentric curricula in Africa (Journal of Decolonising Disciplines, 2020)
This paper applies a social realist ontology in conceptualising Afrocentric curricula in South African universities. The analysis considers South African media reports related to students’ demands for decolonised curricula. The methodology involved textually analysing various historic educational incidents in South Africa, as well as theories associated with Afrocentrism. The analysis highlights that to develop decolonised and Afrocentric curricula, simultaneous consideration is required of the powers of social structures, including race and class, African culture, as well as the agency of students and academics. The analysis concludes that for Afrocentric and decolonised curricula to emerge, it is essential to incorporate the histories, aspirations and cultural affiliations of Africans, who werepreviously marginalised in the nation’s tertiary system. Furthermore, this research highlights that within structures of academic disciplines, it is essential to incorporate African academics and students in developing curricula to create learning experiences which enable a sense of belonging for all students in our universities.
Keywords: #RhodesMustFall movement; Afrocentric curricula; social realist ontology; curriculum